Do we really collaborate effectively in the operating theatre? A cross- sectional study in two hospitals in Greece - Patelarou, Athina; Laliotis, Aggelos; Sifaki Pistola, Dimitra; Marinaki, Sofia; Androulaki, Zacharenia; Tsiou, Chrysoula; Brokalaki, Hero (International Journal of Advanced Nursing Studies, 2014)
The aim of this study was to translate the Disagreement and Aggression in the Operating Theatre Scale (DAOTS) into Greek and investigate the frequency of perceived conflicts, the sources of disagreement and the suggested methods of coping with them within and among professional groups in operating theatres in Greece. The results of this study support the reliability and validity of the DAOTS. The majority of the respondents had witnessed episodes of aggressive behaviour and/or disagreement during the last six months. Physicians more frequently revealed an aggressive behaviour towards a colleague, while nurses were found to be witnesses of a conflict between different professional teams. Daily/weekly disagreements among respondents about availability of equipment, theatre time, changes in the list order and availability of surgical staff were reported. Additionally, hospital type and years of professional experience are considered to affect the prevalence of exposure to a disagreement.